A spatial approach to intersectoral labor and wage mobility - Flisikowski, Karol (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The article presents the problem of the application of spatial weight matrix based on economic distance in spatial analysis of the intersectoral mobility of labor and wage. The spatial weight matrix expresses potential spatial interactions between the researched regions and forms a basis for further construction of spatial econometric model. Calculations of economic distance were based on the level of chosen measure of labor or wage mobility (respectively), whereas in the spatial model data of their chosen determinants were used (such as the level of unemployment, the average earnings, the level of institutionalism, the index of wage or income inequality). Wide time spectrum of the analysis was obtained thanks to the measure of mobility based on a transition probability matrix estimated with the use of the analysis of Markov processes for aggregated data. Because of the availability of homogeneous, highly aggregated sectoral data only for the period 1994–2010, the analyses were performed for 19 selected OECD countries.